2020
DOI: 10.3389/fimmu.2020.01816
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin G Suppresses Heat Shock Protein (HSP)-70 Expression and Enhances the Activity of HSP90 and Proteasome Inhibitors

Abstract: Intravenous immunoglobulin G (IVIgG) is approved for primary immunodeficiency syndromes but may induce anti-cancer effects, and while this has been attributed to its anti-inflammatory properties, IgG against specific tumor targets may play a role. We evaluated IVIgG alone, and with a Heat shock protein (HSP)-90 or proteasome inhibitor, using multiple myeloma and mantle cell lymphoma (MCL) cells in vitro, and with the proteasome inhibitor bortezomib in vivo. IVIgG inhibited the growth of all cell lines tested, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…We considered the idea that heat shock gene downregulation in our pinguecula specimens might be related to the high upregulation of IgG gene expression we observed in pinguecula. Searching the literature, we found one study reporting the downregulation of HSPA1A in tumor cells by intravenous administration of IgG, due to high titers of anti-HSPA1A antibodies [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…We considered the idea that heat shock gene downregulation in our pinguecula specimens might be related to the high upregulation of IgG gene expression we observed in pinguecula. Searching the literature, we found one study reporting the downregulation of HSPA1A in tumor cells by intravenous administration of IgG, due to high titers of anti-HSPA1A antibodies [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since there is a correlation between inflammation and tumours, it is likely that intravenous immunoglobulin G can slow down the growth of tumours due to their anti-inflammatory capacity. Confirming this, Jones et al [75] demonstrated that intravenous immunoglobulin G has now been shown to contain IgG that block HSP70-1, thus inhibiting the growth of tumour cells both using MM and mantle cell lymphoma cells in vitro and with co-administering bortezomib in vivo.…”
Section: Hmgb1-induced Chemoresistancementioning
confidence: 85%
“…8 In addition to its known immunomodulatory effects, IVIG has also been found to exhibit antitumor and antimetastatic activity in both human and animal models. 9,10 This has been observed in a wide array of malignancies including soft tissue sarcomas, melanoma, and thymus cancer and is thought to be dose dependent. The proposed mechanisms behind the antitumor activity of IVIG are diverse and include modulation of macrophage polarization via FcγRIII (CD16), FcγRIV, and the FcRγ chain, suppression of heat shock protein (HSP)-70 expression, enhancement of HSP90 inhibitor activity, increased secretion of IL-12, increased natural killer cell activity, and inhibition of matrix metalloproteinase-9.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Further, it has also been found to boost the antitumor activity of agents such as proteasome inhibitors in multiple myeloma, with combination therapy with IVIG noted to be superior to bortezomib or carfilzomib alone. 9 To date, neither the effect, if any, of IVIG in metastatic RCC nor its interaction with ICIs has been described. However, given that the efficacy of checkpoint inhibition hinges upon a functional immune system, it is plausible that the addition of IVIG may actually be advantageous.…”
Section: Discussionmentioning
confidence: 99%